Copper and sulfur co-lattice doped nano zero-valent iron as well as preparation method and application thereof
By introducing copper and sulfur into nano zero-valent iron to form a eutectic lattice doping structure, the problem of poor stability of nano-zero-valent iron is solved, the reactivity and conductivity are improved, the efficient removal of pollutants is achieved, and the avoidance of copper contamination.
Patent Information
- Application Number
- CN202411402214.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-09
AI Technical Summary
In practical applications, nano zero-valent iron has problems such as poor stability, easy agglomeration and passivation, which affects its dispersion and reactivity in water.
By introducing copper and sulfur, the nano -zero -price iron material doped by copper and sulfur lattice is formed. The use of sulfur is used as a "bridge" to increase the amount of copper income to enhance the conductivity and stability of the material.
It has significantly improved the stability and reaction activity of materials, enhances the ability to remove trichloroethylene and fluorinnib in groundwater. At the same time, it avoids copper pollution and reflects the advantages of green environmental protection.
Smart Images

Figure HDA0005075595240000011 
Figure HDA0005075595240000021 
Figure HDA0005075595240000031
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of functional nano materials and technologies, and in particular relates to a copper-sulfur eutectic lattice doped nano zero-valent iron and a preparation method and application thereof. Background Art
[0002] Nano-Zero-Valent Iron (nFe 0 ) has shown significant potential in the field of environmental remediation, especially in the treatment of soil and groundwater pollutants, due to its excellent reduction ability and high specific surface area. 0 It has special advantages in separating and stabilizing pollutants such as organic chlorides, inorganic anions, and heavy metals [YZ Liu, et al. Nat. Nanotechnol. 16 (2021) 197-205; M. Li, et al. Appl. Catal. B 263 (2020) 118364; WX Zhang, et al. J. Nanopart. Res. 5 (2003) 323-332.]. However, nFe 0 There are also some challenges in practical applications, such as poor stability, easy agglomeration and easy passivation [XH Guan, et al. Water Res. 75 (2015) 224-248.], which will increase its transportation and storage costs, reduce its dispersibility in water, its reactivity with pollutants and its selectivity.
[0003] Regulating the crystal structure and coordination environment of iron-based metals is an emerging strategy to break the trade-off between reactivity and selectivity [D. Chen, et al. Environ. Sci. Technol. 57 (2023) 17178-17188.]. Recently, significant progress has been made in lattice engineering research based on iron nanomaterials. This strategy enhances the performance of materials by simultaneously regulating the geometric structure and the microscopic environment of iron [XH Hu, et al. Nature Water 2 (2024) 84-92.]. In zero-valent iron (Fe 0 ) particles, the doping of foreign atoms can affect the Fe 0 The body-centered cubic (BCC) crystal structure and the coordination environment of the central iron. For example, doping with boron (B) or sulfur (S) can make Fe 0 The lattice expands, which helps the release of electrons, thereby accelerating electron transfer and enhancing reaction activity; at the same time, phosphorus (P) and S can induce Fe 0Nanocracks are generated in the particles, accelerating electron transfer and promoting reaction activity. [JHQu, et al. P. Natl. Acad. Sci. USA. 120 (2023) e2304552120; K. Wei, et al. Adv. Funct. Mater. 32 (2022) 2200498.]. However, the actual doping amount of heteroatoms is easily limited. For example, the actual sulfur doping rate of sulfide nano zero-valent iron, which has been popular in the past decade, is only about one-third of the dosage (<37%) [J. Xu, et al. Accounts Mater. Res. 2 (2021) 420-431.].
[0004] Although there have been many studies on nFe 0 There are many modification measures, such as bimetallic, sulfidation, surface coating, and composite with porous materials, but few have been reported from nFe 0 Based on the characteristics of the element itself, the research on its modification is carried out. 0 The main Fe element is modified and designed from the perspective of ferrophilicity [AG Christy, et al. Eur. J. Mineral. 30 (2018) 193-204.], and the Cu element, which is strongly sulfophilic and weakly ferrophilic, is introduced into the Fe lattice, combining the characteristics of the S element that is both sulfophilic and ferrophilic. The lattice doping amount of Cu is significantly increased. Using copper chloride as the copper source and sodium dithionite as the sulfur source, a nano zero-valent iron material doped with copper and sulfur eutectic lattice is synthesized by a simple one-step method. The material retains the crystal characteristics of nano zero-valent iron and has super hydrophobicity; the actual sulfur doping amount is increased while the lattice copper amount is increased; the change in elemental composition improves the conductivity of the material itself. Therefore, whether it is the life of the material in water, the stability in the air, or the reactivity and selectivity to trichloroethylene or florfenicol in groundwater, it has been significantly improved. In addition, copper can be almost fully doped, so no additional copper pollution will be caused by the introduced copper source, which reflects the green environmental protection advantage of this design. In short, this invention provides a new design idea and technical method reference for lattice engineering modified nanomaterials, especially iron-based nanomaterials. Summary of the invention
[0005] The purpose of the present invention is to address the deficiencies of the prior art and provide a copper-sulfur eutectic lattice doped nano zero-valent iron and a preparation method and application thereof.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing copper-sulfur eutectic lattice doped nano zero-valent iron, comprising the following steps:
[0008] Step 1: Dissolve anhydrous ferric chloride in deionized water to make Fe 3+ Stock solution;
[0009] Step 2: Dissolve cupric chloride dihydrate in deionized water to make Cu 2+ Stock solution;
[0010] Step 3: Prepare the Fe 3+ Stock solution and Cu prepared in step 2 2+ The stock solution is mixed to form a metal mixed solution, in which Cu 2+ and Fe 3+ The molar ratio is 0.01 to 0.1:1; the mixture is stirred and mixed thoroughly at a speed of 100 to 500 rpm using a rotating stirring rod under a nitrogen environment;
[0011] Step 4: dissolving sodium dithionite and sodium borohydride in oxygen-free deionized water at a mass ratio of 0.02 to 0.35:1 to obtain a sulfur solution;
[0012] Step 5: Add the sulfur solution prepared in step 4 to the fully stirred metal mixed solution at a rate of 3-10 mL / min. 2- and metal mixed solution Fe 3+ The molar ratio of is 0.14 to 0.28:1, and during the dropwise addition, the metal mixed solution is stirred under a nitrogen environment and reacts for 15 to 30 minutes;
[0013] Step 6: After the reaction is completed, the obtained material is separated by a magnet and washed three times with oxygen-free deionized water;
[0014] Step 7: Dry the material obtained in step 6 under vacuum at 30-80° C. for 4-12 hours, and react for 0-2 hours after cooling to 25° C. to obtain a dry material;
[0015] Step 8: Grind the dried material prepared in step 7 into powder to obtain copper-sulfur eutectic lattice doped nano zero-valent iron.
[0016] In a second aspect, the present invention also provides a copper-sulfur eutectic lattice doped nano zero-valent iron.
[0017] In a third aspect, the present invention also provides an application of copper-sulfur eutectic lattice doped nano zero-valent iron, wherein the copper-sulfur eutectic lattice doped nano zero-valent iron can be used for efficient dehalogenation of trichloroethylene or florfenicol in groundwater.
[0018] Furthermore, the application comprises the following steps:
[0019] (1) Taking actual groundwater as the reaction system to simulate actual groundwater pollution;
[0020] (2) injecting trichloroethylene or florfenicol into a closed anaerobic reaction bottle containing aerated and deoxygenated groundwater to obtain a trichloroethylene or florfenicol contaminated solution;
[0021] (3) placing the copper-sulfur eutectic lattice-doped nano zero-valent iron material into a sealed oxygen-free reaction bottle containing trichloroethylene or florfenicol pollutants in step (2);
[0022] (4) Place the reaction bottle containing the materials and pollutants in step (3) on a rotator and rotate it.
[0023] Furthermore, the concentration of trichloroethylene in the trichloroethylene contaminated solution in step (2) is 76 μmol / L.
[0024] Furthermore, the concentration of the florfenicol contaminated solution in step (2) is 0.15 to 0.3 mmol / L.
[0025] Furthermore, the dosage of the copper-sulfur eutectic lattice doped nano zero-valent iron material in step (3) can be 0.5-2 g / L.
[0026] Furthermore, the rotator setting conditions in step (4) are 25° C., 30-80 rpm.
[0027] The beneficial effects of the present invention are:
[0028] 1) The preparation method of the eutectic lattice-doped nano zero-valent iron material is a one-step method, which is simple and easy to operate;
[0029] 2) The preparation method can simultaneously achieve doping of transition metal copper and sulfur;
[0030] 3) This method can significantly increase the actual sulfur doping amount of eutectic lattice-doped nano-zero-valent iron;
[0031] 4) This method can significantly increase the amount of copper incorporated into the nano-zero-valent iron lattice;
[0032] 5) This method will not cause copper pollution due to the introduction of copper salts;
[0033] 6) The material has super hydrophobicity and also improves its electrical conductivity;
[0034] 7) The stability of the material, including its lifespan in water and stability in air, has been significantly improved;
[0035] 8) The material can enhance the removal capacity of trichloroethylene and florfenicol pollutants in groundwater. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The present invention is a flow chart of a method for preparing nano zero-valent iron doped with copper and sulfur eutectic lattice;
[0037] Figure 2 This is the X-ray diffraction test pattern;
[0038] Figure 3 TEM morphology and element distribution diagram;
[0039] Figure 4 is the actual Cu / Fe and S / Fe molar ratio diagram, where Figure 4 (a) is the actual Cu / Fe molar ratio diagram, Figure 4 (b) is the actual S / Fe molar ratio diagram;
[0040] Figure 5 is the water contact angle diagram;
[0041] Figure 6 is the fitted resistance diagram;
[0042] Figure 7 is the water stability diagram;
[0043] Figure 8 is the air stability diagram;
[0044] Fig. 9 is the concentration variation with time, where Fig. 9 (a) is the concentration of trichloroethylene in the reaction system changing with time. Fig. 9 (b) is a graph showing the concentration of florfenicol in the reaction system changing with time. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0046] The present invention provides a method for preparing copper-sulfur eutectic lattice doped nano zero-valent iron, comprising the following steps:
[0047] Step 1: Dissolve anhydrous ferric chloride in deionized water to make Fe 3+ Stock solution;
[0048] Step 2: Dissolve cupric chloride dihydrate in deionized water to make Cu 2+ Stock solution;
[0049] Step 3: Prepare the Fe 3+ Stock solution and Cu prepared in step 2 2+The stock solution is mixed to form a metal mixed solution, in which Cu 2+ and Fe 3+ The molar ratio is 0.01 to 0.1:1; the mixture is stirred and mixed thoroughly at a speed of 100 to 500 rpm using a rotating stirring rod under a nitrogen environment;
[0050] Step 4: dissolving sodium dithionite and sodium borohydride in oxygen-free deionized water at a mass ratio of 0.02 to 0.35:1 to obtain a sulfur solution;
[0051] Step 5: Add the sulfur solution prepared in step 4 to the fully stirred metal mixed solution at a rate of 3-10 mL / min. 2- and metal mixed solution Fe 3+ The molar ratio of is 0.14 to 0.28:1, and during the dropwise addition, the metal mixed solution is stirred under a nitrogen environment and reacts for 15 to 30 minutes;
[0052] Step 6: After the reaction is completed, the obtained material is separated by a magnet and washed three times with oxygen-free deionized water;
[0053] Step 7: Dry the material obtained in step 6 under vacuum at 30-80° C. for 4-12 hours, and react for 0-2 hours after cooling to 25° C. to obtain a dry material;
[0054] Step 8: Grind the dried material prepared in step 7 into powder to obtain copper-sulfur eutectic lattice doped nano zero-valent iron.
[0055] The present invention also provides an application of copper-sulfur eutectic lattice doped nano zero-valent iron, wherein the copper-sulfur eutectic lattice doped nano zero-valent iron can be used for efficient dehalogenation of trichloroethylene or florfenicol in groundwater.
[0056] The concentration of trichloroethylene in the trichloroethylene contaminated solution in step (2) is 76 μmol / L.
[0057] The concentration of the florfenicol contaminated solution in step (2) is 0.15-0.3 mmol / L.
[0058] The dosage of the copper and sulfur eutectic lattice doped nano zero-valent iron material in step (3) can be 0.5 to 2 g / L.
[0059] The rotator setting conditions in step (4) are 25° C., 30-80 rpm.
[0060] Example 1 A copper-sulfur eutectic lattice doped nano zero-valent iron (1Cu-S-nFe 0 )
[0061] Step 1: Dissolve 57.93 g of anhydrous ferric chloride in 1000 mL of deionized water to make a concentration of 20 g / L Fe 3+ Stock solution;
[0062] Step 2: Dissolve 6.08 g of cupric chloride dihydrate in 500 mL of deionized water to make a concentration of 12.10 g / L Cu 2+ Stock solution;
[0063] Step 3: Take 100 mL of Fe prepared in step 1 3+ Stock solution and 5 mL of Cu prepared in step 2 2+ The stock solution was placed in a 1000 mL three-necked flask, and 95 mL of oxygen-free deionized water was added to prepare a metal mixed solution; in the metal mixed solution, Cu 2+ and Fe 3+ The molar ratio was 0.01:1; deoxygenation was continued under nitrogen atmosphere, and a rotating stirring rod was used to stir and mix thoroughly at a speed of 400 rpm;
[0064] Step 4: Dissolve 6.8 g of sodium borohydride and 0.44 g of sodium dithionite in 200 mL of oxygen-free deionized water to obtain a sulfur solution;
[0065] Step 5: The sulfur solution prepared in step 4 is added dropwise into the fully stirred metal mixed solution through a constant pressure funnel at a drip rate of 7 mL / min. 2- and metal mixed solution Fe 3+ The molar ratio of is 0.14:1, and the metal mixed solution is stirred under nitrogen environment during the dropwise addition, and the reaction is carried out for 25 minutes;
[0066] Step 6: After the reaction is completed, the obtained material is separated by a magnet and washed three times with oxygen-free deionized water;
[0067] Step 7: The material obtained in step 6 is dried under vacuum at 60°C for 8 hours, and after cooling to 25°C, a slow oxidation reaction is performed for 2 hours to obtain a dry material;
[0068] Step 8: In an anaerobic glove box, use an agate mortar to grind the dry solid obtained in step 7 into fine powder and package it for storage, thereby obtaining a copper-sulfur eutectic lattice doped nano zero-valent iron material.
[0069] In Example 1, Cu 2+ and Fe 3+ The molar ratio of Cu-S-nFe is 0.01:1, so the copper-sulfur eutectic prepared in this embodiment is doped with nano zero-valent iron as a low-copper material, which is marked as 1Cu-S-nFe 0 .
[0070] Example 2 A copper-sulfur eutectic lattice doped nano zero-valent iron (10Cu-S-nFe 0 )
[0071] Step 1: Dissolve 57.93 g of anhydrous ferric chloride in 1000 mL of deionized water to make a concentration of 20 g / L Fe 3+ Stock solution;
[0072] Step 2: Dissolve 6.08 g of cupric chloride dihydrate in 500 mL of deionized water to make a concentration of 12.10 g / L Cu 2+ Stock solution;
[0073] Step 3: Take 100 mL of Fe prepared in step 1 3+ Stock solution and 50 mL of Cu prepared in step 2 2+ The stock solution was placed in a 1000 mL three-necked flask, and 50 mL of oxygen-free deionized water was added to prepare a metal mixed solution; in the metal mixed solution, Cu 2+ and Fe 3+ The molar ratio was 0.1:1; deoxygenation was continued under nitrogen atmosphere, and a rotating stirring rod was used to stir and mix thoroughly at a speed of 400 rpm;
[0074] Step 4: Dissolve 6.8 g of sodium borohydride and 0.44 g of sodium dithionite in 200 mL of oxygen-free deionized water to obtain a sulfur solution;
[0075] Step 5: The sulfur solution prepared in step 4 is added dropwise into the fully stirred metal mixed solution through a constant pressure funnel at a drip rate of 7 mL / min. 2- and metal mixed solution Fe 3+ The molar ratio of is 0.14:1, and the metal mixed solution is stirred under nitrogen environment during the dropwise addition, and the reaction is carried out for 25 minutes;
[0076] Step 6: After the reaction is completed, the obtained material is separated by a magnet and washed three times with oxygen-free deionized water;
[0077] Step 7: The material obtained in step 6 is dried under vacuum at 60°C for 8 hours, and after cooling to 25°C, a slow oxidation reaction is performed for 2 hours to obtain a dry material;
[0078] Step 8: In an anaerobic glove box, use an agate mortar to grind the dry solid obtained in step 7 into fine powder and package it for storage, thereby obtaining copper and sulfur eutectic lattice doped nano zero-valent iron.
[0079] In Example 2, Cu 2+ and Fe 3+The molar ratio of Cu-S-nFe is 0.1:1, so the copper-sulfur eutectic lattice doped nano zero-valent iron prepared in this embodiment is a high-copper material, marked as 10Cu-S-nFe 0 .
[0080] The preparation methods of the copper-sulfur eutectic lattice doped nano zero-valent iron provided in Examples 1 and 2 are both "one-step methods". The flow chart of the preparation method is as follows: Figure 1 As shown in FIG. 1 , the obtained nanometer zero-valent iron material is doped with copper and sulfur eutectic lattice. Pure nanometer zero-valent iron and nanometer zero-valent iron materials doped with copper or sulfur are prepared by the same method. The difference is whether Cu-containing 2+ Stock solution or sulfur solution, and add Cu 2+ The amount of stock solution. The pure nano zero-valent iron material is marked as nFe 0 , sulfur-doped nano zero-valent iron material is labeled S-nFe 0 , low copper doped nano zero-valent iron material is labeled as 1Cu-nFe 0 (Cu 2+ and Fe 3+ The molar ratio is 0.01:1), and the high copper-doped nano zero-valent iron material is marked as 10Cu-nFe 0 (Cu 2+ and Fe 3+ The molar ratio is 0.1:1).
[0081] Application Example 1X-ray diffraction (XRD) test experiment
[0082] The copper-sulfur eutectic lattice doped nano zero-valent iron (1Cu-S-nFe 0 and 10Cu-S-nFe 0 ) and pure nano-zero-valent iron, copper alone and sulfur-doped nano-zero-valent iron materials (nFe 0 , 1Cu-nFe 0 、10Cu-nFe 0 and S-nFe 0 ) to conduct X-ray diffraction test, the test results are as follows Figure 2 shown.
[0083] from Figure 2 It can be seen that all nano zero-valent iron materials retain Fe 0 However, the nano-zero-valent iron material doped with copper or sulfur (1Cu-nFe 0 、10Cu-nFe 0 、S-nFe 0 , 1Cu-S-nFe 0 and 10Cu-S-nFe 0 ) relative to pure nano zero-valent iron (nFe0 ) has a slight shift in peak position, and the sulfur-doped nano-zero-valent iron (S-nFe 0 , 1Cu-S-nFe 0 and 10Cu-S-nFe 0 ) The peak position shift is more obvious, indicating that both copper and sulfur can be doped into nFe 0 The lattice of sulfur is 0 Further comparison revealed that when high copper doping (Cu 2+ and Fe 3+ molar ratio of 0.1:1), in the absence of sulfur doping (10Cu-nFe 0 ), there will be an obvious peak of single copper, indicating that copper is doped into nFe 0 The amount of lattice is limited; however, this situation is not the case when sulfur is co-doped (10Cu-S-nFe 0 ), has been significantly improved, and there is almost no single copper peak, indicating that sulfur can help copper dope into nFe 0 lattice and increase the copper doping into nFe 0 This result shows that the strategy of modifying and designing nano zero-valent iron based on elemental properties, i.e., iron- and sulfur-philicity, is feasible; using sulfur, which has both iron- and sulfur-philicity, as a "bridge" to enhance copper with strong sulfur-philicity and doping nFe 0 The amount of lattice is effective.
[0084] Application Example 2 Transmission Electron Microscope (TEM) Test Experiment
[0085] The copper-sulfur eutectic lattice doped nano zero-valent iron (1Cu-S-nFe 0 and 10Cu-S-nFe 0 ) and pure nano-zero-valent iron, copper alone and sulfur-doped nano-zero-valent iron materials (nFe 0 , 1Cu-nFe 0 、10Cu-nFe 0 and S-nFe 0 ) was used for transmission electron microscopy testing, and the material morphology and element distribution were imaged and analyzed by combining high-angle annular dark field (HAADF) and X-ray energy dispersive spectroscopy (EDS). The results are shown in Figure 3 shown.
[0086] from Figure 3 It can be seen that the material morphology does not change significantly before and after copper or sulfur doping, and is irregular ellipsoidal, but the particle size becomes significantly larger when sulfur is doped. From the distribution of elements, although iron, copper and sulfur are evenly distributed on the material particles, when there is no sulfur doping (1Cu-nFe 0 and 10Cu-nFe 0), the copper element is still distributed in the area without material; while when sulfur is co-doped, the distribution of copper element is almost only in the material particle area (1Cu-S-nFe 0 and 10Cu-S-nFe 0 This result is consistent with the XRD test results, indicating that sulfur, which has both iron and sulfur affinity, can enhance the copper with strong sulfur affinity and dope nFe 0 The amount of lattice.
[0087] Application Example 3: Test of actual Cu / Fe molar ratio and actual S / Fe molar ratio
[0088] The copper-sulfur eutectic lattice-doped nano zero-valent iron (1Cu-S-nFe 0 and 10Cu-S-nFe 0 ) and pure nano-zero-valent iron, copper alone and sulfur-doped nano-zero-valent iron materials (nFe 0 , 1Cu-nFe 0 、10Cu-nFe 0 and S-nFe 0 ) was dissolved in 10 mL of aqua regia and digested overnight. After dilution with deionized water, it was sent to an inductively coupled plasma optical emission spectrometer (ICP-OES) to detect the content of copper, sulfur and iron elements. The actual Cu / Fe molar ratio was obtained as shown in the figure. Figure 4 (a) shows the actual S / Fe molar ratio. Figure 4 (b) as shown.
[0089] from Figure 4 (a) It can be seen that the actual Cu / Fe molar ratio of the copper-sulfur eutectic lattice doped nano zero-valent iron is consistent with the theoretical Cu / Fe molar ratio input during preparation, indicating that the added copper can be fully incorporated into the synthesized copper-sulfur eutectic lattice doped nano zero-valent iron; it is desirable to increase the lattice sulfur incorporation in nano zero-valent iron by introducing copper with strong sulfur affinity, and it will not cause copper pollution due to the copper source added during the synthesis process. Combining the analysis results of XRD and TEM, it can be concluded that under the condition of the same copper doping amount, the amount of copper incorporated into the lattice can be increased by sulfur that has both iron affinity and sulfur affinity. From Figure 4 (b) It can be seen that with the increase of the incorporation amount of copper with strong sulfur affinity, the actual S / Fe molar ratio in the copper-sulfur eutectic lattice doped nano zero-valent iron increases, indicating that the incorporation of copper can increase the lattice incorporation amount of sulfur, thereby reducing the ineffective consumption of sulfur reagents and reducing the risk of sulfur reagent pollution.
[0090] Application Example 4 Water Contact Angle Experiment
[0091] In an anaerobic glove box, the copper-sulfur eutectic lattice doped nano zero-valent iron (1Cu-S-nFe0 and 10Cu-S-nFe 0 ) and pure nano-zero-valent iron, copper alone and sulfur-doped nano-zero-valent iron materials (nFe 0 , 1Cu-nFe 0 、10Cu-nFe 0 and S-nFe 0 ) were made into a 6 mm diameter sheet, then dried at 60 °C for 8 h under vacuum, taken out after cooling to 25 °C, and the water contact angle was quickly measured with a water drop angle instrument to test the hydrophobicity of each material. The water contact angle of each material is as follows Figure 5 shown.
[0092] from Figure 5 It can be seen that compared with nFe 0 and single copper-doped nano zero-valent iron materials (1Cu-nFe 0 and 10Cu-nFe 0 ), the water contact angles of the other materials are all greater than 90°, and 1Cu-S-nFe 0 The water contact angle of 1Cu-S-nFe 0 As a superhydrophobic material, its lifespan in water and air stability should be significantly improved, which will help reduce transportation and storage costs.
[0093] Application Example 5: Electrochemical Experiment
[0094] 100 mg of the copper-sulfur eutectic lattice-doped nano zero-valent iron (1Cu-S-nFe 0 and 10Cu-S-nFe 0 ) and pure nano-zero-valent iron, copper alone and sulfur-doped nano-zero-valent iron materials (nFe 0 , 1Cu-nFe 0 、10Cu-nFe 0 and S-nFe 0 ) is placed on the titanium mesh and pressed on the titanium mesh using a hydraulic tablet press. The titanium mesh is taken out and clamped on the working electrode clamp, and an electrochemical impedance spectroscopy (EIS) test is performed in a three-stage cell with 10 mM NaCl as the electrolyte. The resistance results after fitting analysis of the test data are as follows Figure 6 shown.
[0095] from Figure 6 It can be seen that the resistance decreases significantly with the addition of copper or sulfur, and the copper and sulfur co-doping (1Cu-S-nFe 0and 10Cu-S-nFe 0 ) has a higher resistance than copper alone or sulfur doped (1Cu-nFe 0 、10Cu-nFe 0 and S-nFe 0 ) is lower, indicating that the nano zero-valent iron material doped with copper and sulfur eutectic lattice (1Cu-S-nFe 0 and 10Cu-S-nFe 0 ) has better conductivity and faster electron transfer rate, that is, the co-incorporation of copper and sulfur gives nano zero-valent iron higher electrocatalytic activity, reflecting the excellent conductivity and activity advantages of copper and sulfur eutectic lattice doped nano zero-valent iron materials, which will be beneficial to the removal of pollutants.
[0096] Application Example 6: Water Life and Air Stability Experiment
[0097] Life test in water: 100 mg of the copper-sulfur eutectic lattice-doped nano zero-valent iron (1Cu-S-nFe 0 and 10Cu-S-nFe 0 ) and pure nano-zero-valent iron, copper alone and sulfur-doped nano-zero-valent iron materials (nFe 0 , 1Cu-nFe 0 、10Cu-nFe 0 and S-nFe 0 ) was placed in a 170 mL reaction bottle containing 100 mL of oxygen-free deionized water, the headspace was purged with nitrogen and then sealed, and the reaction bottle was then placed on a rotator, 500 μL of headspace gas was extracted at a preset time point for hydrogen detection, and the Fe 0 →H2 conversion, and finally the Fe content in the depleted material is obtained 0 The length of time the content is maintained is the material's lifespan in water.
[0098] Air stability: The remaining Fe 0 The content and water contact angle change were used as indicators to consider air stability. 10 mg of the copper-sulfur eutectic lattice-doped nano zero-valent iron (1Cu-S-nFe 0 and 10Cu-S-nFe 0 ) and pure nano-zero-valent iron, copper alone and sulfur-doped nano-zero-valent iron materials (nFe 0 , 1Cu-nFe 0 、10Cu-nFe 0 and S-nFe 0 ) was dissolved in 10 mL of hydrochloric acid and digested for 4 to 6 h. After complete digestion, 500 μL of headspace gas was taken for hydrogen detection and the Fe 0 +HCl→Fe 2++H2 conversion, the Fe of the material is obtained 0 Content, by comparing with the original material Fe 0 Content comparison, the remaining Fe 0 The water contact angle test method is the same as that of Application Example 4 except that the material is changed to a material aged in air for different time periods.
[0099] from Figure 7 It can be seen that the nano zero-valent iron material (1Cu-S-nFe 0 ), and the shortest is the copper-doped nano zero-valent iron material (1Cu-nFe 0 ), which matches the hydrophobicity and electron transfer capacity of the material. 0 and 1Cu-nFe 0 , and pure nano zero-valent iron material (nFe 0 ) are all improved, and 1Cu-S-nFe 0 The electron transfer ability is stronger than that of 1Cu-nFe 0 , but due to 1Cu-S-nFe 0 It is a super hydrophobic material and 1Cu-nFe 0 It is a hydrophilic material, so it is the hydrophilic 1Cu-nFe that reacts easily with water and is then corroded and consumed. 0 Similarly, from Figure 8 It can be seen that thanks to 1Cu-S-nFe 0 The super hydrophobicity of the membrane was also improved, and its stability in the air was also improved. During the 30-day monitoring, the residual Fe 0 The content and water contact angle change are minimal, and more than 80% of Fe can be preserved 0 The content and maintenance of hydrophobic properties indicate that during transportation and storage, it is less demanding on the environment and storage conditions, which helps to reduce costs.
[0100] Application Example 7: Removal of trichloroethylene (TCE) and florfenicol (FF) in groundwater
[0101] 100 mg of the copper-sulfur eutectic lattice-doped nano zero-valent iron (1Cu-S-nFe 0 and 10Cu-S-nFe 0 ) and pure nano-zero-valent iron, copper alone and sulfur-doped nano-zero-valent iron materials (nFe 0 , 1Cu-nFe 0 、10Cu-nFe 0 and S-nFe 0) was placed in a 170mL reaction bottle containing 100mL of oxygen-free groundwater, the headspace was purged with nitrogen and then sealed, followed by injection of 250uL of 27.8mmol / L (mM) TCE stock solution or 1mL of 15mM FF stock solution, so that the initial concentration of TCE was 76umol / L (μM) or the initial concentration of FF was 0.15mM; the reaction bottle was then placed on a rotator. The changes in TCE and FF were detected at preset time points. For TCE, 100μL of headspace gas was extracted for gas phase detection to detect residual TCE; for FF, 1mL of liquid was extracted for liquid phase detection to detect residual FF. The concentration changes of TCE and FF during the reaction are shown in the following table. Fig. 9 (a) and Fig. 9 (b) as shown.
[0102] from Fig. 9 (a) and Fig. 9 (b) It can be seen that the concentrations of TCE and FF in the nano zero-valent iron material doped with copper and sulfur eutectic lattice (1Cu-S-nFe 0 ) reaction system, the decrease was the fastest. Even in the groundwater system with relatively complex components, after 120h of reaction, 1Cu-S-nFe 0 It can also remove more than 80% of TCE; and for FF, almost 100% of FF can be removed by 1Cu-S-nFe 0 The complete removal reflects the advantages of copper and sulfur eutectic lattice doped nano zero-valent iron materials in the treatment of TCE and FF contaminated groundwater and its practical application potential.
[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing copper-sulfur eutectic lattice doped nano zero-valent iron, characterized in that: The following steps are involved: Step 1: Dissolve anhydrous ferric chloride in deionized water to make Fe 3+ Stock solution; Step 2: Dissolve cupric chloride dihydrate in deionized water to make Cu 2+ Stock solution; Step 3: Prepare the Fe 3+ Stock solution and Cu prepared in step 2 2+ The stock solution is mixed to form a metal mixed solution, in which Cu 2+ and Fe 3+ The molar ratio is 0.01 to 0.1:1; the mixture is stirred and mixed thoroughly at a speed of 100 to 500 rpm using a rotating stirring rod under a nitrogen environment; Step 4: dissolving sodium dithionite and sodium borohydride in oxygen-free deionized water at a mass ratio of 0.02 to 0.35:1 to obtain a sulfur solution; Step 5: Add the sulfur solution prepared in step 4 to the fully stirred metal mixed solution at a rate of 3-10 mL / min. 2- and metal mixed solution Fe 3+ The molar ratio of is 0.14 to 0.28:1, and during the dropwise addition, the metal mixed solution is stirred under a nitrogen environment and reacts for 15 to 30 minutes; Step 6: After the reaction is completed, the obtained material is separated by a magnet and washed three times with oxygen-free deionized water; Step 7: Dry the material obtained in step 6 under vacuum at 30-80° C. for 4-12 hours, and react for 0-2 hours after cooling to 25° C. to obtain a dry material; Step 8: Grind the dried material prepared in step 7 into powder to obtain copper-sulfur eutectic lattice doped nano zero-valent iron.
2. A copper-sulfur eutectic lattice doped nano zero-valent iron prepared by the method as claimed in claim 1.
3. An application of the copper-sulfur eutectic lattice doped nano zero-valent iron according to claim 2, characterized in that: The copper and sulfur eutectic lattice doped nano zero-valent iron can be used for efficient dehalogenation of trichloroethylene or florfenicol in groundwater.
4. The use according to claim 3, characterized in that: The application consists of the following steps: (1) Taking actual groundwater as the reaction system to simulate actual groundwater pollution; (2) injecting trichloroethylene or florfenicol into a closed anaerobic reaction bottle containing aerated and deoxygenated groundwater to obtain a trichloroethylene or florfenicol contaminated solution; (3) placing the copper-sulfur eutectic lattice-doped nano zero-valent iron material into a sealed oxygen-free reaction bottle containing trichloroethylene or florfenicol pollutants in step (2); (4) Place the reaction bottle containing the materials and pollutants in step (3) on a rotator and rotate it.
5. The use according to claim 4, characterized in that: The concentration of trichloroethylene in the trichloroethylene contaminated solution in step (2) is 76 μmol / L.
6. The use according to claim 4, characterized in that: The concentration of the florfenicol contaminated solution in step (2) is 0.15-0.3 mmol / L.
7. The use according to claim 4, characterized in that: The dosage of the copper and sulfur eutectic lattice doped nano zero-valent iron material in step (3) can be 0.5 to 2 g / L.
8. The use according to claim 4, characterized in that: The rotator setting conditions in step (4) are 25° C., 30-80 rpm.
Citation Information
Patent Citations
Nickel and sulfur co-doped nano zero-valent iron as well as preparation method and application thereof
CN114682260A
Vulcanized nano zero-valent iron with controllable sulfur content and form as well as preparation method and application of vulcanized nano zero-valent iron
CN114799199A
Synergistic oxidation-reduction agent for polluted groundwater remediation
CN116589069A
Omitted
KR101717127B1
Organic wastewater treatment method based on multi-element co-doped tio 2 NANO photocatalytic material
WO2022047813A1